External Dacryocystorhinostomy: Characteristics and Surgical Outcomes in Patients with and without Previous Dacryocystitis. (18th December 2013) - Rabina, Gilad; Golan, Shani; Neudorfer, Meira; Leibovitch, Igal
Abstract : Objective . To compare pre- and postoperative characteristics and surgical success rates of patients with and without previous episodes of dacryocystitis, who underwent external dacryocystorhinostomy (DCR) for nasolacrimal duct obstruction (NLDO). Methods . The medical files of all patients who underwent external DCR between 2006 and 2011 in our institution were reviewed. The retrieved data of patients with and without previous episodes of dacryocystitis were compared. Surgical success was determined by postoperative followup of at least 6 months. Results . A total of 185 patients with NLDO underwent external DCR of whom 152 (100 females and 52 males, mean age 67 ± 15 years) met the inclusion criteria. Sixty had previous episodes of dacryocystitis and 92 did not. Left-side obstruction was more common than right-side obstruction among patients with previous episodes of dacryocystitis (48.3% versus 31.7%, resp., P = 0.031 ). Glaucoma patients were significantly more likely to develop dacryocystitis than patients without glaucoma (P = 0.002 ). The success rate of external DCR was 94.4% for patients with previous episodes of dacryocystitis and 86.7% for patients without (P = 0.337 ). Conclusions . The surgical outcomes of external DCR in patients with or without a previous episode of dacryocystitis were similar. Patients with glaucoma and NLDO had a significantly higher risk of developing dacryocystitis.